Experiments on a videotape atom chip: fragmentation and transport studies - Llorente Garcia, I, I; Darquie, B; Curtis, E; Sinclair, C; Hinds, E (IOP Publishing, 2010)
This paper reports on experiments with ultracold rubidium atoms confined in microscopic magnetic traps created using a piece of periodically magnetized videotape mounted on an atom chip. The roughness of the confining potential is studied with atomic clouds at temperatures of a few μK and at distances between 30 and 80 μm from the videotape-chip surface. The inhomogeneities in the magnetic field created by the magnetized videotape close to the central region of the chip are characterized in this way. In addition, we demonstrate a novel transport mechanism whereby we convey cold atoms confined in arrays of videotape magnetic micro-traps over distances as large as ~1 cm parallel to the chip surface. This conveying mechanism enables us to survey the surface of the chip and observe potential-roughness effects across different regions.